(untitled) (Journal of the College of Basic Education, 2022)
The research’s goal knowing : Impact of the modified strategy of (Murder) in scientific thinking for the intermediate-stage (first-class) in science subject . To verify the research ’s goal, the following hypothesis has been formulated: There is no statistically significant difference at the level of significance (0.05) between the scores average of the experimental group ’s students who studied according to the modified strategy of (Murder) and the scores average of the control group’s students who studied according to the usual method in scientific thinking testing. The researcher has chosen the experimental design with two groups (experimental and control), and those with the post-test of the two variables of scientific thinking testing, one of which controls the other partially. The research ’s community represented the intermediate– stage –first – class students in "That Al-Sawari " secondary School for Girls, for the academic year (2019-2020), whose number is (103) students , (33, 33, 37) students representing the classrooms (A, B, C), respectively. Two sections ( A- B) have been chosen randomly as a sample for research, and section (B) has been selected to represent the experimental group and the number of its members (33) female students and section (A) to represent the control group and the number of its members (33) female students. After excluding the female students failed in the two groups, the number of research sample ’s students in the two groups is (65) students by (33) female students for the experimental group and (32) female students for the control group. The two groups have been treated in variables (previous achievement of science, intelligence test, testing previous information in the science subject, scientific thinking testing) the scientific subject has been determined in the first two units ( the subject , periodic table) from the science book for the intermediate stage ,first – class , 2nd edition, Ministry of Education for the year 2017AD. The experiment has been applied to the first semester of the academic year (2019-2020), the researcher has taught the research ’s two groups by herself, as she has prepared the necessary teaching plans (18) plans for the experimental group according to the modified strategy of (Murder), and the same for the control group according to the normal method . The behavioral goals for the first two units have been formulated and reached (226) behavioral goals represented in the six levels of Bloom’s classification of the cognitive domain, respectively (remembering, assimilation, application, analysis, synthesis, evaluation). To verify the aim of the research, the first research tool has been prepared for scientific thinking testing consisting of (20) position formed by the multiple choice type, each position four paragraphs indicates to position which measures one of the steps in scientific thinking, in order (Defining the problem, Assumption, Hypothesis testing, Explanation or conclusion, Generalization) Each position has four paragraphs, have been verified and proven by using the (Quder Richardson equation-20) and the consistent coefficient of scientific thinking testing reached (81%), in addition to using psychometric properties, so , the research ’s results ,by using T-test for two independent samples, have indicated the following: - - The students of the experimental group who studied according to the modified strategy of " Murder " outperformed the students of the control group who studied according to the usual method of scientific thinking testing , as the calculated (t) reached (4,312), while the tabular value of the (t) reached (2,000) at the level of significance (0 , 05). From these results, the researcher has concluded that teaching with the modified strategy of " Murder " affected the female students’ scientific thinking testing in the science subject, as the size of impact reached (0,150) greatly compared to the standard (0.14) for achievement, while the size of impact reached for scientific thinking (0,233) greatly, consequently the researcher has made a number of recommendations, including to benefit science teachers in daily study plans for teaching the intermediate –stage ( first –class ) students with the subject of science according to the modified strategy of " Murder ".